DEVELOPMENT OF LEARNING TOOLS THROUGH TEACHERS AND STUDENTS CENTERED APPROACHES - Rahmat, Ade; Cahyadi, Ashadi; Iskandar, Iskandar (UNIVERSITAS NEGERI MAKASSAR, 2021)
The purpose of this study was to determine the validity, practicality and effectiveness of badminton learning tools. The research method used was the Research and Development (R&D) method with the ADDIE Model (analysis-Design-Develop-Implementation-Evaluation). Research subjects and validators in this study is a material experts, media experts and students totaling 30 students. The data collection tools used questionnaires and badminton skills tests. The data analysis technique used is the average questionnaire formula and badminton skills test. The results showed (1) the teaching materials developed in this study met the valid criteria (2) The teaching materials developed in this study met the practical criteria. (3) The teaching materials developed in this study meet the criteria of being effective.